2009
DOI: 10.1063/1.3079521
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Al interface intermixing and the role of Ti, V, and Zr as a stabilizing interlayer at the interface

Abstract: The chemical mixing at the "Al on Fe" and "Fe on Al" interfaces was studied by molecular dynamics simulations of the layer growth and by 57 Fe M€ ossbauer spectroscopy. The concentration distribution along the layer growth direction was calculated for different crystallographic orientations, and atomically sharp "Al on Fe" interfaces were found when Al grows over (001) and (110) oriented Fe layers. The Al/Fe(111) interface is also narrow as compared to the intermixing found at the "Fe on Al" interfaces for any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The comprehensive work of Buchanan et al 2 found 0.9 nm intermixing length for the "Al on Fe" interface. From the latest RBS and XRR results, 4 2.06 nm width of the "Al on Fe" interface is deduced, contrary to the atomically sharp interface we observe. Most of the former M€ ossbauer experiments 6-10 studied multilayered samples and therefore were not suitable to make a clear distinction between the two types of interfaces.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The comprehensive work of Buchanan et al 2 found 0.9 nm intermixing length for the "Al on Fe" interface. From the latest RBS and XRR results, 4 2.06 nm width of the "Al on Fe" interface is deduced, contrary to the atomically sharp interface we observe. Most of the former M€ ossbauer experiments 6-10 studied multilayered samples and therefore were not suitable to make a clear distinction between the two types of interfaces.…”
Section: Discussionmentioning
confidence: 67%
“…The Fe-Al system is selected for this purpose since the largely different chemical mixing at the top and the bottom interface has been established by different experimental methods. [2][3][4] The interface mixing in Fe-Al multilayers has been studied intensively by MS, [5][6][7][8][9][10] as well, and due to the outstanding properties of the alloy system for industrial applications, the M€ ossbauer parameters of the different alloy phases and the dependence of the hyperfine fields (HFs) on the number of Al neighbors in the bcc phase are well studied. 8 MD simulations have already been performed for the Fe(001)/Al (Al on top of Fe) and Al(001)/Fe (Fe on top of Al) interfaces, 11,12 and these indeed show an asymmetry of the top and bottom Fe interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…7 Ultrathin Fe/Ti/Al(001) film system has been studied for decades due to its applications to magnetic sensors and hard disk devices. [8][9][10][11] In Fe/Ti/Al(001) thin film systems for magnetic memory applications, the Ti adlayers with thickness from 1 monolayer (ML) to 3ML are introduced * Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%